FOREIGN EXPERIENCE IN ORGANIZING THE MONITORING OF WATER FUND LANDS - Jo‘rayev Akbar Rahmonqulovich (Uzbekistan Open Conference, 2026)
This article examines the experience of advanced foreign countries in organizing the monitoring system of water fund lands, focusing on their institutional and technological approaches and water resource management strategies. Using the examples of the USA, the European Union, Japan, and Israel, the study analyzes organizational mechanisms of monitoring, the use of digital technologies, remote sensing, GIS, and IoT systems. Recommendations and proposals applicable to the conditions of Uzbekistan are also provided.
Keywords: Remote sensing; satellite; nanotechnologies; sensors; water quality; transboundary; water management; water level; hydrological stations